Online teaching in psychotherapy training: a qualitative study revealing challenges and strategies from lecturers’ perspectives - Springinsfeld, Constanze; Pfatrisch, Nina; Akgün, Adalet; Scholtus, Victoria; Tilkidzhieva, Elitsa; Fiegl, Jutta; Jesser, Andrea (Frontiers in Education, 2025)
Despite a growing body of research on online teaching in psychotherapy training, existing studies focus on students’ experiences, leaving the perspectives of lecturers underexplored. This study addresses this gap by investigating lecturers’ views on the transition to online teaching during the COVID-19 pandemic. Data were collected through 13 semi-structured expert interviews with lecturers at the Faculty of Psychotherapy Science at Sigmund Freud Private University, conducted between November 2022 and December 2023. Thematic content analysis was employed to analyze the data. The findings indicate that online teaching is suitable for specific components of psychotherapy training, such as theoretical foundations, research methods, supervision, and individual self-experience. However, practice-oriented training and group self-experience, which depend on direct personal interaction, were significantly hindered by the online format. Lecturers identified challenges in fostering engagement, sustaining attention, and maintaining relational depth, largely due to the lack of non-verbal cues and shared physical spaces. The study concludes that relational skills, central to psychotherapy training, are best developed through in-person interaction. Nonetheless, a blended learning approach that combines online and face-to-face teaching is recommended. Online tools provide flexibility and efficiency, particularly for theoretical components, but their successful integration requires thoughtful course design and targeted lecturer training. The findings underscore the need for a balanced approach to optimize the strengths of both online and traditional teaching formats in psychotherapy training.